2019
DOI: 10.1093/nar/gkz099
|View full text |Cite
|
Sign up to set email alerts
|

SAM68 interaction with U1A modulates U1 snRNP recruitment and regulates mTor pre-mRNA splicing

Abstract: Src associated in mitosis (SAM68) plays major roles in regulating RNA processing events, such as alternative splicing and mRNA translation, implicated in several developmental processes. It was previously shown that SAM68 regulates the alternative splicing of the mechanistic target of rapamycin ( mTor ), but the mechanism regulating this process remains elusive. Here, we report that SAM68 interacts with U1 small nuclear ribonucleoprotein (U1 snRNP) to promote splicing at the 5′ splice si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 71 publications
(107 reference statements)
1
23
0
Order By: Relevance
“…This study focused on the neuronal isoform selection in 3′ UTR by SAM68 and demonstrated their functional aspects through the identification of a novel target IL1RAP in neurons (Figure 5). Very recently, two articles also elucidated the interaction between SAM68 and U1 small nuclear ribonucleoprotein particle (snRNP) as a global mechanism underlying ALE regulation by SAM68 (Naro et al., 2019, Subramania et al., 2019), supporting our findings in the CNS. U1 snRNP prevents premature transcript termination by inhibition of cryptic PASs (Berg et al., 2012, Kaida et al., 2010).…”
Section: Discussionsupporting
confidence: 85%
“…This study focused on the neuronal isoform selection in 3′ UTR by SAM68 and demonstrated their functional aspects through the identification of a novel target IL1RAP in neurons (Figure 5). Very recently, two articles also elucidated the interaction between SAM68 and U1 small nuclear ribonucleoprotein particle (snRNP) as a global mechanism underlying ALE regulation by SAM68 (Naro et al., 2019, Subramania et al., 2019), supporting our findings in the CNS. U1 snRNP prevents premature transcript termination by inhibition of cryptic PASs (Berg et al., 2012, Kaida et al., 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Sam68 promotes exon 2 inclusion ( Fig. 2d, e) and it cooperates with the spliceosomal U1snRNP in exon recognition 28,22 . Analysis of testes from juvenile Sam68 knockout mice (P10) showed a significant reduction in Spo11 exon 2 inclusion (Fig.…”
Section: A Reduced Rnapii Elongation Rate Promotes Splicing Of Spo11αmentioning
confidence: 94%
“…RNAPII processivity within the transcription unit can also influence AS regulation [7][8][9]22 . Since RNAPII activity is modulated during male meiosis 12,23 , we asked whether Spo11 splicing is sensitive to changes in the RNAPII elongation rate.…”
Section: A Reduced Rnapii Elongation Rate Promotes Splicing Of Spo11αmentioning
confidence: 99%
“…The functional AS outcomes of different splicing regulators have been convincingly documented in WAT adipogenesis. Sam68, highly involved in cellular RNA processing events and signal transduction pathways [ 70 , 89 ], has been demonstrated in adipocyte development to increase the number of early adipocyte progenitors by controlling AS of the mechanistic target of mTOR signaling [ 66 , 68 ]. The Sam68 binding sites often localize near AS junctions within pre-mRNAs, so they often engage in regulating neighboring alternative exon usage and splice site selection as either splicing enhancers or silencers [ 69 ].…”
Section: Introductionmentioning
confidence: 99%